2019
DOI: 10.1186/s12889-019-7015-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dengue fever outbreak in Dire Dawa administration city, October, 2015, Ethiopia - case control study

Abstract: Background Dengue Fever (DF) is underrecognized mosquito borne viral disease prevalent in tropical and subtropical regions. In 2013, Ethiopia reported the first confirmed DF outbreak in Dire Dawa city which affected 11,409 people. During the outbreak investigation, we determined factors associated with DF and implemented control measures. Methods We conducted a 1:2 un-matched case control study from October 7–15/2015. Case was any person with fever of 2–7 days and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 11 publications
8
44
2
Order By: Relevance
“…This study also revealed that participants not wearing long sleeved cloths (OR=19.48; 95%CI; 5.70 -66.6; P-value <0.001) had 20 times the risk of acquiring Dengue Fever infection as compared to the users. Similar study was conducted in Diredewa in 2015 was shows that there has association between the wearing type of cloth and the risk of acquiring the Dengue Fever infection 11 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This study also revealed that participants not wearing long sleeved cloths (OR=19.48; 95%CI; 5.70 -66.6; P-value <0.001) had 20 times the risk of acquiring Dengue Fever infection as compared to the users. Similar study was conducted in Diredewa in 2015 was shows that there has association between the wearing type of cloth and the risk of acquiring the Dengue Fever infection 11 .…”
Section: Discussionsupporting
confidence: 61%
“…The model result shows those who have open water containers (stagnant water) around their houses were 15 times (adjusted OR = 15.2: 95% CI: 3.33 -68.8) more at risk to have the disease. In consistence with this, case control study conducted in Dire Dawa during 2015 showed that people living in the areas where open water container had high morbidity rate of dengue feve 11 . Similar study from Vietnam identified that people living near stagnant water like ponds, lakes or open sewers had higher rates of dengue fever morbidit 10 .…”
Section: Discussionmentioning
confidence: 62%
“…stephensi larvae, suggesting that these two vectors share larval habitats. Dengue is a growing public health concern in Ethiopia, particularly in eastern Ethiopia, where major outbreaks were reported in 2013 [18,19] and 2015 [20]. With the finding of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…stephensi and Aedes in the same water body [42]. Outbreaks of chikungunya [43], dengue [44], and yellow fever [45] were recently reported from Ethiopia within the same geographic setting. The WHO recommends the use of integrated vector management [46] – an adaptive and evidence-based approach to vector control which utilizes vector control interventions from within and outside the health sector that may include larval source management of both An.…”
Section: Discussionmentioning
confidence: 99%